Fast Timing Detectors and Applications in Cosmic Ray Physics and Medical Science - Christophe Royon; William d’Assignies D.; Florian Gautier; Tommaso Isidori; Nicola Minafra; Alexander Novikov (Instruments, 2023)
We use fast silicon detectors and the fast sampling method originally developed for high energy physics for two applications: cosmic ray measurements in collaboration with NASA and dose measurements during flash beam cancer treatment. The cosmic ray measurement will benefit from the fast sampling method to measure the Bragg peak where the particle stops in the silicon detector and the dose measurement is performed by counting the number of particles that enter the detector.